DUKUNGAN ARAB SAUDI TERHADAP KUDETA MESIR TAHUN 2013 - Kaza "; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes Saudi Arabia’s support against Egypt military coup upon, the first Egyptian Moslem President elected by democracy. This support is convinced by King Abdullah bin Abdul Aziz by various media, Saudi Arabian Government pledges fresh money six day after Morsi’s coup.This study applies qualitative research method with library research. The data sources are from books, journals, and the Internet. This study uses security theory and nation-state level of analysis.This Research explain that Saudi Arabia under King Abdullah is the first leader supporting morsi’s coup. The Support is emerged by the fact that Muslim Brotherhood dominated in Egyptian political, it would be ideological treat to Saudi Arabia governance.Keywords: Coup, Mohammad Morsi, Muslim Brotherhood, Ideological treat, Support